Hydrogen Generating Cartridge Unit and Portable Hydrogen Power Generator - KIM, DONG HWAN (2017)
The present invention relates to a portable hydrogen power generator. The portable hydrogen power generator comprises: a main housing which includes a cartridge accommodation unit and a stack accommodation unit; a hydrogen reaction cartridge which is detachably accommodated in the cartridge accommodation unit and accommodates a hydrogen-impregnated metal that reacts with water to generate hydrogen; a hydrogen generating cartridge unit which has a water cartridge storing water; a pump which pumps and supplies the water from the inside of the water cartridge into the hydrogen reaction cartridge; and a fuel cell stack which is accommodated in the stack accommodation unit, and receives hydrogen from the hydrogen generating cartridge unit to generate electricity. Accordingly, the portable hydrogen power generator can be conveniently carried around and be used as an emergency power source in emergency situations including power outages. Moreover, the hydrogen generating cartridge unit is adapted to be easily mounted on or unmounted from the main body of the hydrogen power generator, thus facilitating the exchange of fuel. 본 발명은 포터블 수소발전기에 관한 것이다. 포터블 수소 수소발전기는, 카트리지수용부와 스택수용부를 갖는 본체하우징, 상기 카트리지수용부에 착탈가능하게 수용되며, 물과 반응하여 수소를 발생시키는 수소함침금속을 수용한 수소반응카트리지와, 물을 저장하는 워터카트리지를 갖는 수소생성카트리지유니트, 상기 워터카트리지 내의 물을 상기 수소반응카트리지 내부로 공급하도록 펌핑하는 펌프, 및 상기 스택수용부에 수용되어 상기 수소생성카트리지유니트로부터의 수소를 공급받아 전기를 발생하는 연료전지스택으로 구성된 것을 특징으로 한다. 이와 같은 본 발명 포터블 수소발전기는 간편하게 휴대가 가능하면서 정전 등의 비상시에 비상용 전원으로 사용할 수 있다. 또한, 수소생성카트리지유니트를 수소발전기 본체에서 장착 및 탈락이 쉽게 이루어지므로 연료의 교환이 용이하다.